Pengaruh partisipasi anggaran terhadap kinerja manajerial: komitmen organisasi dan ketidakpastian lingkungan sebagai moderasi - HARYO SUPARMUN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
The research objective is to get empirical evidence about the effect of budget participation on managerial performance as well as the influence of organizational commitment and environmental uncertainty on the relationship between budgetary participation and managerial performance. Respondents were used in data analysis as much as 65 managers in hotels in Jakarta and Yogyakarta. Hypothesis testing using moderating regression analysis. The results showed that the effect of budget participation on managerial performance is signifficant. While the organization's commitment and environmental uncertainty does not affect the relationship between budgetary participation and managerial performance.